Respuesta :
Answer: n = -6
Step-by-step explanation:
Step 1: Simplify both sides of the equation.
12= −1/3n +10
Step 2: Flip the equation.
−1/3n +10=12
Step 3: Subtract 10 from both sides.
−1/3n +10−10=12−10
−1/3n =2
Step 4: Multiply both sides by 3/(-1).
(3/−1) x (-1/3n) = (3/-1) x (2)
n=−6
12 = n/-3 + 10
2 = n/-3 (subtract both sides by 10)
-6 = n (multiply both sides by -3)
Therefore the value of n is -6.
2 = n/-3 (subtract both sides by 10)
-6 = n (multiply both sides by -3)
Therefore the value of n is -6.